Region (JSTOR)
This is a peer-reviewed international journal that explores the history and current political, economic, and social affairs of the entire former Soviet bloc. In particular, the journal focuses on various facets of transformation at the local and national levels in the aforementioned region, as well as the changing character of their relationships with the rest of the world in the context of glocalization
Keywords: History, Slavic Studies